Litter production and decomposition in reforestation and native forest areas in southern Amazon - Bello, Ozias Cunha (2022)
The diversity of forest species is an intrinsic characteristic of the Amazon biome, with litter being the main responsible for the largest portion of nutrients returned to the soil. Thus, the objective of this study was to quantify the annual production of burlap and to determine the rate of decomposition over one year, comparing the results in the different study environments. The study was developed in the municipality of Humaitá-AM. For the evaluation of the litter production, ten cone collectors were randomly installed in each study area. Each litter sample was placed separately in properly identified paper bags and taken to the laboratory and dried in a forced air circulation oven at 65 ° C. The litter decomposition rate was estimated by mass loss analysis using litter bags. Litter production with the highest annual average was 8,03 Mg ha-1 year -1 for the native forest environment, with no significant difference for the other study areas. Among the fractions of the litter that contributed the most to the leaf, reaching a higher average percentage in the year of 72,1% for the environment of reforestation with teak (Tectona grandis L.). The decomposition of litter occurred more rapidly (0.0025 g g-1 day) in the reforestation environment with genipap (Genipa americana L.), requiring 277,26 days to decompose half of the leaf material.